Falite Qito and Narcissism (Psychoanalytic and critical reading) - Abdulrahman, Hussein O. (Humanities Journal of University of Zakho, 2018)
Folklore literature with its various genres and elements is to be considered as source of different information about life, tradition, materials, and type of philosophy and view of Kurdish individual. Falite Qito is one of the Kurdish folkloric stories, and it is a sort of Kurdish nation’s biography in which it demonstrates tradition, chivalry, bravery along with evilness and corruption. Undoubtedly, literature as its structure, either literary meaning or content, is not left from phycology whether it is related to a psychological state of the writer or reader and character as well. So, each literary text could be read and analyses from different prospective and psychological states. Accordingly, this study is a psychoanalytic study which attempts to read the psychological state of Falite Qito’s mind as a main character in folkloric story of Falite Qito. This study entitled “Falite Qito and Narcissism (Psychoanalytic and critical reading)” it investigates the personality of Falite Qito and his psychological state of mind in terms of mental disordering and narcissism or his further self-love and status in the society. The study is prepared based on the descriptive analysis and ultimately it concludes that Falite Qito is mentally turned to be narcissist, and all his behaviors and actions are the outcomes of that narcissism.